Methodology of mastering the informatization features in the professional training of specialists - Фабричев, В. А. (Proceedings of National Aviation University, 2002)
The methodology of informatics teaching, stages of the educational program in informatics and its teaching and methodological support are considered. It is shown that the proposed methodology allows for the simultaneous capture of methods and means of informatics together with signs of a specialty during the entire period of study